Operating Systems / Internals and Design Principles - Stallings, William (Prentice Hall, 1998)
A unique operating systems textbook that blends a comprehensive theoretical foundation for understanding operating systems with real-world applications. Preface, Background, Operating System Overview, Processes, Process Description and Control, Threads and SMP and Microkernels, Memory, Memory Management, Virtual Memory, Scheduling, Uniprocessor Scheduling, Multiprocessor and Real-Time Scheduling, Input/ Output and Files, I/O Management and Disk Scheduling, File Management, Distributed Systems, Distributed Process Management, Security, Appendices, Glossary, References, Index.